The Cardiorenal Syndrome: Making the Connection. (23rd September 2010) - Viswanathan, Gautham; Gilbert, Scott
Abstract : The heart and the kidneys share responsibility for maintaining hemodynamic stability and end-organ perfusion. Connections between these organs ensure that subtle physiologic changes in one system are tempered by compensation in the other through a variety of pathways and mediators. In the setting of underlying heart disease or chronic kidney disease, the capacity of each organ to respond to perturbation caused by the other may become compromised. This has recently led to the characterization of the cardiorenal syndrome (CRS). This review will primarily focus on CRS type 1 where acute decompensated heart failure (ADHF) results in activation of hemodynamic and neurohormonal factors leading to an acute drop in the glomerular filtration rate and the development of acute kidney injury. We will examine the scope and impact of this problem, the pathophysiology associated with this relationship, including underperfuson and venous congestion, diagnostic tools for earlier detection, and therapeutic interventions to prevent and treat this complication.